Phyllis Zaballero - Roces, Alfredo R. (Philippine : LIVEMORE, INC., 2013)
Biography of Phyllis del Rosario Zaballero, a woman painter and visual artist from Philippines.
Includes index.
Keywords: Zaballero, Phyllis del Rosario; Artists -- Philippines -- Biography